Reusable Personal Protective Equipment Viewed Through the Lens of Sustainability - Laurence J. Walsh (Elsevier, 2024)
From early 2020 the COVID-19 pandemic drove dramatic increases in the production and use of single use disposable masks, respirators and gowns, and highlighted the vulnerability of supply chains for these items. This paper explores the impacts of the rising demands for these single use items through the lens of sustainability, by collating data on the carbon footprint and other impacts, and then discussing challenges, solutions, and future perspectives. Polypropylene and other key synthetic fibre components of these items are not biodegradable, and persist in the environments for prolonged periods generating microplastics as they degrade slowly. Various methods have been shown to allow limited repeated use of surgical masks and respirators, and this has spurred the development of masks and respirators designed for many cycles of reuse. Parallel discussions around gowns reveal that reuseable gowns offer many advantages for performance as well as reduced environmental impact. At the local dental clinic level, those making purchasing decisions should consider impacts of their product choices on the environment. Such impacts occur from manufacture, transport, and disposal of PPE, and from degradation within the environment. Regulators need to encourage use of reuseable items and facilitate this through local guidelines, while at the international level, more work is needed to develop uniform standards for reuseable masks, respirators and gowns.